2014
DOI: 10.4049/jimmunol.1400336
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of B Cell–Mediated Immune Suppression through CD73 Expression and Adenosine Production

Abstract: Immune suppression by regulatory T (Treg) cells and regulatory B (Breg) cells is a critical mechanism to limit excess inflammation and autoimmunity. IL-10 is considered to be the major mediator of B cell-induced immune suppression. Here, we report a novel mechanism for immune suppression through adenosine generation by B cells. We identified a novel population of B cells that expresses CD73 as well as CD39, two ecto-enzymes that together catalyze the extracellular dephosphorylation of adenine nucleotides to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 68 publications
8
103
0
Order By: Relevance
“…Finally, there is evidence that B cells would regulate immunity not only through cytokine production but also via surface molecules, such as CD39, CD73 and Programmed death-ligand 1 (PD-L1). Indeed, a novel population of B cells has been shown to regulate colitis in an IL-10-independent manner but dependent on the expression of CD39 and CD73 [29]. CD39 is an ectonucleoside triphosphate diphosphohydrolase-1 and CD73 is an ecto-5 0 -nucleotidase which hydrolyze exogenous adenosine triphosphate (ATP) to adenosine 5 0 -monophosphate (AMP) and finally produce immunosuppressive adenosine (ADO) [30][31][32].…”
Section: Regulatory B Cells: Phenotypes and Suppression Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is evidence that B cells would regulate immunity not only through cytokine production but also via surface molecules, such as CD39, CD73 and Programmed death-ligand 1 (PD-L1). Indeed, a novel population of B cells has been shown to regulate colitis in an IL-10-independent manner but dependent on the expression of CD39 and CD73 [29]. CD39 is an ectonucleoside triphosphate diphosphohydrolase-1 and CD73 is an ecto-5 0 -nucleotidase which hydrolyze exogenous adenosine triphosphate (ATP) to adenosine 5 0 -monophosphate (AMP) and finally produce immunosuppressive adenosine (ADO) [30][31][32].…”
Section: Regulatory B Cells: Phenotypes and Suppression Mechanismsmentioning
confidence: 99%
“…CD39 is an ectonucleoside triphosphate diphosphohydrolase-1 and CD73 is an ecto-5 0 -nucleotidase which hydrolyze exogenous adenosine triphosphate (ATP) to adenosine 5 0 -monophosphate (AMP) and finally produce immunosuppressive adenosine (ADO) [30][31][32]. In the dextran sulfate sodium salt-induced colitis murine model, transfer of ADOproducing CD73 + B1 cells conferred resistance to the colitis susceptible CD73 À/À mice [29]. In addition, experiments performed by Saze and collaborators [33] demonstrated that upon activation, human B cells increase their expression of CD39 and acquire the capability to downregulate proliferation of autologous CD4 + or CD8 + T cells.…”
Section: Regulatory B Cells: Phenotypes and Suppression Mechanismsmentioning
confidence: 99%
“…B1 cells in particular express cell surface CD73, an ectoenzyme critically important for generating adenosine [30]. We found that hepatic numbers of both CD73 + B1a and B1b B cells significantly increase post-αGalCer administration ( Fig.…”
Section: Cd)mentioning
confidence: 72%
“…In a series of experiments we addressed potential mechanisms whereby B cell depletion augments αGalCer-induced liver injury, including altering iNKT cell activation [34] and proinflammatory cytokine production (specifically IL-4 and TNFα) [2,5,6], enhancing hepatic recruitment of neutrophils and/or γδ T cells (both implicated in αGalCer-induced hepatitis) [11,12], and the potential loss of B cell derived anti-inflammatory cytokines (IL-10 and/or TGFβ) [13,[15][16][17] or the capacity to generate anti-inflammatory mediators (ie adenosine) [29,30] within the liver.…”
Section: B Cell Depletion Enhances Inkt Cell-driven Liver Injury Via mentioning
confidence: 99%
“…In this sense, it should be noted that endothelial cells express CD39 and CD73 on their surface and can be a source of adenosine [102]. Furthermore, it has recently been demonstrated both in mice and in humans that B-cells express CD39 and CD73, produce adenosine and inhibit T-cell proliferation [103,104]. Likewise, CD56 bright CD16…”
Section: Regulatory T-cells and Adenosinementioning
confidence: 99%